PTH-105 Salvage hepatectomy in failed portal vein embolisation. (22nd June 2015) - Iype, S; Harper, S; Huguet, E; Jah, A
Abstract : Introduction: The traditional approach to induce liver hypertrophy of future liver remnant (FLR) is portal vein embolization (PVE). Portal vein ligation (PVL) was also used with successful outcome. Two stage hepatectomy with Association of Portal vein ligation and Partition of Liver (ALLPS)has been in practice recently. We analyse the cases which failed to achieve sufficient hypertrophy following PVE and has been salvaged by two staged hepatectomy. Method: Our prospective database of 72 cases of PVE over 7 years were analysed and identified 4 cases that didn't achieve sufficient hypertrophy and subsequently underwent two stage hepatectomy. Patient characteristics, volume increase, postoperative complications and outcomes were analysed. Results: All 4 patients had extended right hepatectomy. Two patients had colorectal liver metastasis and the other two had hilar cholangiocarcinoma. The staged resections were carried out at an average of 14 days apart. Patient 1 had an FLR of 18%after PVE that increased to 38% after parenchymal transection (stage 1). Patient 2 had an FLR of 25% after PVE which increased to 39% after stage 1 resection. Patient 3 had FLR of 21% after PVE which increased to 34% after stage 1 resection. Patient 4 had FLR volume of 28% with background chronic liver fibrosis that increased to 36% after stage 1. All patients underwent a R0 resection. One patient had postoperative bile leak. There was no operative mortality. Conclusion: Salvage resection of liver is an effective approach to patients who do not achieve sufficient FLR volume following PVE. Disclosure of interest: None Declared.